Modelos Neuro-Adaptados para Predição de Radiopropagação em Sistemas Móveis Terrestres 10.14209/jcis.2001.2 - Sanches, Mári; Cavalcante, Gervásio (Journal of Communication and Information Systems, 2015)
This work proposes a hybrid model of prediction to the determination of the propagation loss in urban environment cellular mobile systems, constituted of an artificial neural network and an adapted model. These models were implemented and tested starting from a campaign of measurements accomplished in the urban area of Belern of Para city. The mean intensity values of the received sign in this campaign were compared with the values foreseen by the adapted models and their respective hybrid models. having as focus the dependence of the sign received with the distance between transmitter and receiver.